Amyloidosis - Feng, Dali (IntechOpen, 2013)
Amyloidosis is an uncommon disorder characterized by the deposition of extracellular amyloid proteins in tissues. Significant advancement has been made recently, which not only provides insight in to the pathophysiology of the disease but also helps to discover new therapies to fight the deadly disease. If accurate diagnosis and typing are made early, effective or even curative therapies are available. Unfortunately, because of the rarity of the disease and its protean clinical manifestations, patients may be misdiagnosed, especially at early stage of the disease, and this could lead to missed opportunities to effective therapy. The aim of the book is to help readers become familiar with the clinical presentation of amyloidosis and to review the latest diagnostic and therapeutic development.